DCZ3301, a novel aryl-guanidino inhibitor, induces cell apoptosis and cell cycle arrest via suppressing the PI3K/AKT pathway in T-cell leukemia/lymphoma. (23rd April 2018) - Xiao, Wenqin; Li, Bo; Sun, Xi; Yu, Dandan; Xie, Yongsheng; Wu, Huiqun; Chang, Shuaikang; Zhou, Yunfei; Wang, Houcai; Lan, Xiucai; Xu, Zhijian; Shi, Jumei; et al.
Abstract: DCZ3301, a novel aryl-guanidino compound, was previously found to have potent anti-tumor activity in myeloma and B-cell lymphoma. In the present study, we investigated the effects of DCZ3301 on T-cell leukemia/lymphoma cells both in vitro and in vivo via cell proliferation, cell cycle analysis, apoptosis assay, mitochondrial membrane potential (MMP) assay, western blot analysis and tumor xenograft models. We found that DCZ3301 inhibited the viability of T-cell leukemia/lymphoma cells in a dose- and time-dependent manner. DCZ3301-induced G2 /M cell cycle arrest, associated with downregulation of CDK1, cyclin B1, and cdc25C. DCZ3301 also induced cell apoptosis by decreasing MMP in T-cell leukemia/lymphoma cells, but had no significant pro-apoptotic effect on normal peripheral blood mononuclear cells (PBMCs). In addition, DCZ3301-induced apoptosis may be mediated by the caspase-dependent pathway and suppressing the phosphoinositide 3-kinase (PI3K)/AKT pathway. Finally, we showed that DCZ3301 treatment effectively inhibited tumor growth, with no significant side effects, in xenograft mouse models. In conclusion, these results suggest that DCZ3301 may be regarded as a new therapeutic strategy for T-cell leukemia/lymphoma patients.